Hydrological variations associated with geomorphological changes in a sand dune barrier of the Partido de La Costa, province of Buenos Aires - Carretero, Silvina Claudia (2017)
The evolution of land use in San Clemente del Tuyu and Santa Teresita (Partido de La Costa [La Costa District], Buenos Aires , Argentina ) is analysed in association with the increase in population and the presence or absence of a water supply service, in order to assess changes in the hydrological system through time. A multi-temporal analysis was undertaken on Landsat satellite images, differentiating types of land use . Water balances were estimated, and the recharge for each situation was evaluated. An increase in urbanized surface at the expense of the natural sand dune environment can be observed, which entails larger impervious surfaces that are unsuitable for the infiltration and recharge of the aquifer. In both areas, a decrease in groundwater reserves occurred; in Santa Teresita , there was even a deterioration in the chemical quality of water due to sea water intrusion . It can be concluded that the urbanization process has had a negative impact on the water system in the sand dune barrier area, affecting the infiltration and recharge processes. The presence of managed supply systems acquires relevance as a conditioning factor to avoid saltwater intrusion processes. It is essential to implement land-use planning strategies that would protect the areas unaffected by urbanization that may be of use as a reservoir for the future supply of freshwater .